Early Relational Health: Infants' Experiences Living with Their Incarcerated Mothers. (2nd January 2017) - Condon, Marie-Celeste
ABSTRACT: Little is known about the experiences and inner worlds of infants who live with their parents in prison-based residential programs. Infant observation and qualitative methods were used to study the experiences of seventeen infants living with their incarcerated mothers in a women's correctional facility. Glimpses into their inner worlds provide insights into factors that hearten and hinder early relational health. Practitioners and parents can use a relational health approach to recognize and cultivate budding capacities in infant-parent relationships. The researcher discusses the usefulness and relevance of infants' accounts for communities of practice and research.